Postbiotics against pathogens commonly involved in pediatric infectious diseases (2020)
The Sustainable Development goals for 2020 included reducing all causes associated with infant and perinatal mortality in their priorities. The use of compounds with bioactive properties has been proposed as a therapeutic strategy due to their stimulating effect on the host’s immune system. Additionally, biotherapeutic products such as postbiotics, tentatively defined as compounds produced during a fermentation process that support health and well-being, promote intestinal barrier integrity without posing considerable risks to children’s health. Although this is a concept in development, there are increasing studies in the field of nutrition, chemistry, and health that aim to understand how postbiotics can help prevent different types of infections in priority populations such as minors under the age of five. The present review aims to describe the main mechanisms of action of postbiotics. In addition, it presents the available current evidence regarding the effects of postbiotics against pathogens commonly involved in pediatric infections. Postbiotics may constitute a safe alternative capable of modulating the cellular response and stimulating the host’s humoral response.